Epidemiological characteristics of human respiratory syncytial virus infection in Guangzhou city from 2021 to 2024: a surveillance data analysis - Yong LIU; Mingming YAN; Yanhui LIU; Lan CAO; Jiangrong WANG; Tengfei ZHOU; Lei LUO; Mengmeng MA (Zhongguo gonggong weisheng)
ObjectiveTo understand the epidemiological characteristics of human respiratory syncytial virus (HRSV) infection in Guangzhou city. MethodsData were sourced from two parts: national influenza sentinel surveillance and Guangzhou city′s acute respiratory infection cluster surveillance. Sentinel surveillance data, collected from August 2023 to July 2024, included outpatient and emergency department influenza-like illness (ILI) cases and hospitalized severe acute respiratory infection (SARI) cases from four national-level influenza sentinel hospitals in Guangzhou. Cluster surveillance data, from 2021 to 2023, included acute respiratory infection (ARI) clusters caused by HRSV in Guangzhou. Respiratory specimens were collected from cases for multiple respiratory pathogen nucleic acid testing. The HRSV positive detection rate among sentinel surveillance cases was calculated, and indicators such as the HRSV infection attack rate among children in cluster settings were comparatively analyzed. ResultsThe overall HRSV positive detection rate among the included sentinel surveillance cases was 3.75% (51/1 360). Among the positive cases, 68.63% (35/51) were children under 5 years old, with the highest positive detection rate observed in the < 6 months age group (10.29%, 7/68). The HRSV positive detection rate among hospitalized SARI cases in this age group was as high as 31.25% (5/16). Two HRSV epidemics occurred in Guangzhou, one in the summer and autumn of 2023 (August - September) with subtype A as the dominant strain, and the other in the spring of 2024 (February-April) with subtype B. All four monitored HRSV-induced ARI clusters occurred in summer; three in postpartum care centers and one in a childcare facility. The overall attack rate among children was 42.42% (84/198). The overall asymptomatic infection rates among mothers and staff in these facilities were 83.33% (5/6) and 82.35% (14/17), respectively. Positive environmental samples from postpartum care centers were mainly from infant common areas or nursing areas. ConclusionsHRSV epidemics in Guangzhou show clear seasonality. Children under 5 years old, especially infants under 6 months, are the main population affected by HRSV infection and hospitalization. Postpartum care centers and childcare facilities are prone to HRSV clusters. Timely detection of asymptomatic infections and effective environmental cleaning and disinfection are crucial for epidemic control.